Riverine agroforestry systems: Tree diversity and species structure along Lilagar river catchment in Chhattisgarh, India - Arun Kumar Shukla; K.K. Chandra; Rajesh Kumar; Atul Kumar Bhardwaj (Green Technologies and Sustainability)
Riverine agroforestry is essential for maintaining biodiversity, climate-resilient farming as well as maintaining river flow. However, our rivers are drying and diminishing due to increasing anthropogenic activities in the riverine ecosystem. In this study, the riverine agroforestry system along the Lilagar river, Bilaspur, India was compared with the natural forest in terms of tree diversity, structure, and composition. Ten grid points at 10 km intervals along the riverine habitat covering 100 km length of the river were undertaken. A number of trees, IVI, Shannon–Weiner Index, dominance, evenness index, etc., were analysed and compared with both the land use system. Thirty-seven tree species were reported in riverine agroforestry systems, compared to 28 tree species from the natural forest. Tree species belonging to the Fabaceae family dominate in riverine agroforestry while Combetaceae and Anacardiaceae are in the natural forest. Tree density was found 86.25 ha−1in agroforestry and 419.11 trees ha−1in a natural forest. For riverine farmland and natural forests, the Shannon diversity index was 1.69 and 2.38, respectively, whereas the evenness index was measured at 0.473 and 0.703 for these two land use systems. Species dissimilarities were recorded in both the land use system. The results show that riverine agroforestry complements the natural forest for biodiversity conservation and supports in counteracting the loss of tree species from the natural ecosystem. Hence, promoting agroforestry in farmlands should be part of the biodiversity conservation strategy and increase riverine sustainability.